Możliwości analityczne koncepcji społecznego tworzenia rzeczywistości w odniesieniu do homoseksualizmu w Polsce. Refleksje dla poradnictwa - Bartusiak, Marta (Adult Education Discourses, 2020)
The text attempts to indicate the analytical possibilities offered by the concept of the social construction of reality in relation to the phenomenon of homosexuality in the context of Poland. It also points to an important area from the perspective of the counselling discourse, which is the work with homosexual people and people whose relatives have a homosexual sexual orientation. The article consists of three parts. The first one presents the attitude of Polish law and Poles towards homosexuality. Based on reports from research (conducted for example by such institutions as the Centre for Social Opinion Research or the Centre for Research on Prejudice) and the media, both manifestations of homophobia or discrimination and tolerance towards homosexual people are presented. In the second part, the author points to the analytical possibilities offered by the concept of the social construction of reality in relation to the situation of homosexuality in Poland. The questions that can be asked from the perspective of this theory when looking at the phenomenon of homosexuality in Poland are indicated here. The third part deals with the area of providing help to homosexual people and their relatives in a counseling situation. The author refers here both to the tasks that a counsellor has to face when meeting a homosexual person or his relatives in a counselling situation and to the perception of the counselling situation itself from the perspective of Berger and Luckmann’s concept. The text is an introduction to further research into the social state of knowledge about homosexuality and possible changes in reality.